Menumbuhkan Minat Belajar Anak Dengan Memberikan Motivasi dan Belajar Bersama - Mia Aulia Lubis; Ilham Dhani Hasibuan (Yayasan Literasi Sains Indonesia, 2022)
The author did practicum 1 at the North Padang Lawas Social Service Office. While doing activities at the office, the author did a mini project with children sitting in elementary school. This paper intends to review the problem of lack of interest in learning by elementary school students and their solutions. Interest in learning is a very important factor in student success. Because, the role of interest is very big influence on a person's willingness to accept and do an action. If students' interest in learning begins to decline, it can be ascertained that the students concerned are less enthusiastic in participating in a series of learning activities, both in class and at home. Therefore, with an interest in learning students will be able to understand and do assignments with enthusiasm. The solution offered in practical activities is to invite children to study together and provide advice or motivation. The stages used in the micro-level social intervention are the case work stages by Zastrow which consist of: Engagement, assessment, planning/planning, intervention, evaluation and termination.